IGF-1 , Leptin & AIP in relation to Osteoarthritis with and without Diabetes Mellitus Type2 - Ashoor, Lamia S.; Ali, Tariq M.; Hasan, HamidG. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
IGF-1 is a protein produced by the liver in response to growth hormone stimulus.One important key in effectively preventing and treating osteo arthritis, is establishing a healthy balance of IGF-1. Leptin is a hormone produced by adipose tissue, acting as a sensor of fat mass in part of a negative feedback loop that maintains a set point for body fat stores. Leptin plays an important role in the progression of Osteoarthritis (OA), prompting some to classify OA as a metabolic disease. it, has been found in synovial fluid from patients with OA , and are thought to have local effects on joint tissues . Atherogenic index of plasma (AIP) is newly marker of atherogenectiy provide prediction to accelerated development of atherosclerosis in diabetes mellitus patients. Objective This study was designed to find out the variation of some parameters in OA with & without T2DM. Patients and methods This study included ( 88) subjects aged between (40-60) years (all females , newly diagnoses and obese) who were attending the Al- Kadhimiya Teaching Hospital . Baghdad and Al-Mustansiriya University . The enrolled patients were divided to four groups: OA(24) , T2DM (20), OAwithT2DM (24) and control (20) . Venous blood samples from women were taken for laboratory investigation which included : Fasting plasma glucose , lipid profile (TC ,TG , HDLc and LDLc) , IGF-1 , Leptin were measured and Atherogenic index of plasma calculated as molar ratio of log (TG/ HDL-C). Results The current study shows a significant increased atherogenic index , Leptin value , in three patients groups diabetes , osteoarthritis and OAwith DM when compared with control. But IGF-1 level was significantly decreased in the three patients groups T2DM, OA , T2DM with OA when compared with control . Conclusion Osteoarthritis has a direct effect on dislipidemia ,Leptin & AIP value in Diabetes mellitus type2